Factor XIII Val34Leu variant protects against coronary artery disease - Vokó, Zoltán; Bereczky, Zsuzsanna; Katona, Éva; Ádány, Róza; Muszbek, László (Thrombosis and Haemostasis, 2007)
Several studies suggested that Val34Leu variant of factor XIII (FXIII) might have a protective effect against coronary artery disease (CAD), but studies not supporting these findings have also been published. The authors performed a meta-analysis of 16 studies on 5,346 cases and 7,053 controls that investigated the association between Val34Leu polymorphism and CAD defined as history of myocardial infarction or significant stenosis on a coronary artery assessed by coronary angiography. Because of the heterogeneity of the study-specific results, the pooled effect estimates were calculated by a random-effects empirical Bayes model. The combined odds ratios for CAD were 0.82 (95% confidence interval [95% Cl] 0.73, 0.94) for the heterozygotes of the FXIIIVal34Leu variant, 0.89 (95% CI 0.69, 1.13) for the homozygotes, and 0.81 (95% CI 0.70, 0.92) for the heterozygotes and homozygotes combined. The results were essentially the same when only myocardial infarction was considered as outcome. The beneficial effect of the polymorphism might be smaller than the effect estimates obtained in this metaanalysis, because the analysis raised the possibility of publication bias. Data published in the literature suggest that gene-gene and gene-environmental interactions might significantly influence the protective effect of FXIII-AVal34Leu polymorphism.
Keywords: Coronary disease; factor XIII; polymorphism; meta-analysis